1967
DOI: 10.1115/1.3609699
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Damage and Correlations With Material and Fluid Properties

Abstract: A comprehensive set of cavitation damage data has been obtained in a vibratory facility using water, mercury, lithium, and lead-bismuth alloy as test fluids, and covering temperatures ranging from room temperature to 1500 deg F. Materials tested include a wide variety of metals and alloys. From this data a simple, reasonably precise, damage predicting equation has been derived, including only ultimate resilience as a material property, but also corrections for cavitation “thermodynamic effects” and NPSH. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 0 publications
2
27
0
2
Order By: Relevance
“…Good correlation between the mean depth of penetration rate (MDPR) and "ultimate resistance" which is energy per unit volume required to stress the material to the true breaking stress, assuming no plastic deformation occurred, was obtained by Garcia and Hammitt [1]. Endo et al [2] noticed that cavitation damages consisted of pitting by impact fracture and falling off by fatigue failure of surface.…”
Section: Introductionmentioning
confidence: 94%
“…Good correlation between the mean depth of penetration rate (MDPR) and "ultimate resistance" which is energy per unit volume required to stress the material to the true breaking stress, assuming no plastic deformation occurred, was obtained by Garcia and Hammitt [1]. Endo et al [2] noticed that cavitation damages consisted of pitting by impact fracture and falling off by fatigue failure of surface.…”
Section: Introductionmentioning
confidence: 94%
“…Several parameters are known to have a major influence on the erosive potential of the cavitation bubbles: (i) the viscous and surface tension forces of the liquid environment, (ii) the distance of the bubble to the wall interface, (iii) the maximum size of the bubble prior to collapse, and (iv) the adverse pressure gradient to which the bubble is subjected and which causes its collapse. [11] It has been reported that the cavitation erosion resistance of materials, even if it can be regarded as an independent mechanical property of the material itself, [12] depends on mechanical properties and characteristics such as strain energy, [13] ultimate strength, [14] hardness, [15] roughness [16] as well as the strain hardening ability of the material. [17] Thus, extensive research has been carried out elsewhere [18][19][20][21][22][23] in order to find effective correlations between the cavitation erosion rate and the physical properties of the tested fluids as well as the cavitation erosion rate and the mechanical properties of the tested materials.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia and Hammitt [24] offered the correlation for several groups of materials (aluminum alloys, stainless steels, cooper alloys, nickel alloys) describing MDPR by equation: 7Hattori and Ishikura [20] confirmed an impact of tensile strength on the cavitation erosion resistance of steels (Fig. 4).…”
Section: Tensile Strengthmentioning
confidence: 96%